"Build[ing] something which alone we could not have done": International collaborative teaching and learning in language teacher education. (April 2016) - Tanghe, Shannon; Park, Gloria
Abstract: Building on calls to internationalize teacher education and recognizing the under-explored value of international collaboration, we discuss an international collaborative project (ICP) developed and facilitated by two teacher-educators in South Korea and the United States. The study focuses on the teacher-educators' implementation of the ICP as well as four graduate students' experiences with the collaboration. Data from graduate students' written reflections, individual interviews, e-mail messages, course blogs, and teacher-educators' observation reflection journals inform the study. Positioning theory is utilized as an analytical framework to explore the graduate students' intergroup interactions in the project and how these cooperative experiences and positioning patterns facilitated co-construction of meanings. Results indicate the international collaboration enhanced graduate students' intercultural competences and stimulated perspective transformations. Based on findings which emerged from the collaboration, pedagogical considerations for teacher-educators interested in implementing international collaborations are provided.